2015
DOI: 10.1097/bor.0000000000000219
|View full text |Cite
|
Sign up to set email alerts
|

Systemic sclerosis-associated fibrosis

Abstract: Purpose of this review Systemic sclerosis (SSc) is an autoimmune disease with fibrosis seen in multiple organs. While not traditionally regarded as a disease of aging, SSc-associated fibrosis shares many of the hallmarks of aging seen in other age-related fibrotic disorders. Here, we review current literature of the potential role of aging and age-related cellular processes in the development of SSc and fibrosis. Recent findings Accumulating evidence supports a role for immune dysregulation, epigenetic modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 55 publications
(40 reference statements)
0
18
0
Order By: Relevance
“…Autophagy and mitochondrial dysfunction, two other inter-related aging processes, have been implicated in SSc and other fibrotic diseases. Autophagy, a cellular proteostatic mechanism that targets damaged proteins and organelles for lysosomal degradation, and mitochondrial function both decline with aging, and impairments contribute to fibrosis in SSc and IPF as well as in animal models (see [17] for a detailed review).…”
Section: Molecular Mechanisms Of Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…Autophagy and mitochondrial dysfunction, two other inter-related aging processes, have been implicated in SSc and other fibrotic diseases. Autophagy, a cellular proteostatic mechanism that targets damaged proteins and organelles for lysosomal degradation, and mitochondrial function both decline with aging, and impairments contribute to fibrosis in SSc and IPF as well as in animal models (see [17] for a detailed review).…”
Section: Molecular Mechanisms Of Agingmentioning
confidence: 99%
“…Premature and segmental activation of aging may contribute, among other pathologies, to autoimmunity [4], vascular abnormalities [5, 6], and fibrosis [717]. It is therefore not surprising that scleroderma, or systemic sclerosis (SSc), a disease characterized by the triad of autoimmune activation, vasculopathy, and fibrosis, has been described as a disease of accelerated aging [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, age-related biological changes have been observed in sclerosis-associated fibrosis (Luckhardt and Thannickal, 2015), anxiety disorders (Perna et al 2016), Down syndrome (Horvath et al 2015), and schizophrenia (Czepielewski et al 2016). In laboratory studies of HIV, accelerated aging has been observed through increased immune senescence associated with alterations in T-cell generation and gene expression (Boulias et al 2016; Chou et al 2013; Gianesin et al 2016; Pathai et al 2014) and resulting inflammation (for review, see Bhatia et al 2011).…”
mentioning
confidence: 99%
“…There is increasing evidence that SSc skin presents several hallmarks of cellular ageing, such as enhanced production of reactive oxygen species (ROS), methylation abnormalities and impaired autophagy . CCN1 has been associated with skin ageing in several studies .…”
Section: Ccn Proteins and Accelerated Ageingmentioning
confidence: 99%